Hi World: The Virtual Book Learning Integrated Augmented Reality to Increase Knowledge of Covid-19 Prevention in The Learning Process Post-Pandemic Era - Putra , Andika Bagus Nur Rahma; Heong, Yee Mei; Meidyanti , Dewi Sabrina; Rahmawati, Anita (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This research aims to Improve innovation Hi World integrated with AR, Testing The level of attraction of Hi World, and test the level of Hi World's appropriateness for covid-19 patients. This research method is R&D involving the expert of Covid-19 and digital media. The result from this research are: Innovation of Hi World improved to have a good level of appropriateness with a score of 90%; Level of attraction with this book is good with a score of 95%, and Hi world have design choices that are suitable for the requirement that covid-19 patients needs